Short- and long-term effects of pulmonary rehabilitation in mild COPD: a comparison with patients with moderate-to-severe COPD - Jácome, Cristina (2016)
PURPOSE: Pulmonary rehabilitation (PR) is effective in patients with moderate to severe chronic obstructive pulmonary disease (COPD). However, the effects of PR in patients with mild COPD have not yet been established. Thus, this study investigated the short- and long-term effects of PR in patients with mild COPD in comparison with patients with moderate to severe disease. METHODS: A total of 32 patients with mild (group 1) and 29 with moderate to severe (group 2) COPD completed the study. Both groups participated in a 12-week PR program with exercise training and psychosocial support and education. Outcome measures at baseline, 3 (post-PR), 6, and 9 months later included 6-minute walk test (6MWT); Modified Medical Research Council Dyspnea Scale; 1-repetition maximum chest press and knee extension; a brief physical activity assessment; the number of exacerbations in the past 3 months and the St. George Respiratory Questionnaire (SGRQ). RESULTS: Improvements in the 6MWT, chest press, knee extension, and physical activity were observed post-PR (P < .001), with no differences between the 2 groups. Reduction in the number of exacerbations (P < .001) and improvements in the SGRQ total (P < .001) were also observed, however, with greater magnitude in group 2 (P = .029 and P < .001, respectively). Except for peripheral muscle strength (P < .002), all the achieved benefits were sustained at 6 and 9 months (P > .05). CONCLUSIONS: Pulmonary rehabilitation improves exercise tolerance, muscle strength, physical activity, and health-related quality of life and reduces exacerbations in patients with mild COPD as it does in patients with moderate to severe COPD. Moreover, most of these benefits were maintained at 9-month follow-up, suggesting that PR could be part of the management of mild COPD.